Peran Guru dalam Mewujudkan Lingkungan Belajar Inklusif bagi Siswa Tunarungu di Sekolah Dasar - Alfina Mutiara Diaz Fernanda; Yumi Zakiyah; Aulia Luthfi Dewi Pramesta; Choiriyah Widyasari; Minsih Minsih (YASIN, 2026)
The implementation of inclusive education in regular elementary schools still faces various challenges, particularly in accommodating the learning needs of students with hearing impairments. This study aimed to describe the role of classroom teachers in creating an inclusive learning environment for students with hearing impairments. A qualitative descriptive approach with a case study design was employed, with data collected through participant observation, semi-structured interviews, and documentation involving the Grade IV classroom teacher, the principal, and parents at SDN Wonokerto 1. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that the teacher assumes three essential roles: as a learning facilitator through the use of adaptive visual strategies, as a social mediator who fosters empathy and interaction among students, and as an active collaborator with parents and the school. Although facing challenges such as limited mastery of sign language and insufficient supporting facilities, the teacher demonstrates strong dedication and initiative in inclusive teaching practices. This study has implications for strengthening understanding of inclusive education practices in elementary schools and underscores the importance of teacher professional development to support their role in creating a learning environment that is welcoming for students with hearing impairments.